Play-Based Learning: Conceptualization, Benefits, and Challenges of Its Implementation - Haile, Tekli Simon; Ghirmai, Daniel Jambo (European Scientific Journal, ESJ, 2024)
This paper focuses on exploring the conceptualization, benefits, and challenges of implementing play-based learning (PBL) among Eritrean pre-school educators. The study was grounded on the social cognitive theory and a qualitative research approach was applied to explore the research objectives. A semi-structured interview was conducted with nine teachers, six principals, and two pre-primary education curriculum developers. Using inductive approach, interviews were thematically analyzed. The study found discrepancies between participants’ views and their implementation. The findings indicate that most of the participants viewed PBL as incorporating both free play and guided play. Although free play is useful in the overall development of children, this study revealed that it cannot be used effectively as an instrument to teach lessons that have specific academic objectives such as numeracy and literacy skills. Moreover, the researchers sought to investigate the actual practices of PBL. The study found that the majority of educators were placed at the extremes of the Child Adult Involvement Continuum: free play and direct instruction. Furthermore, the results revealed that teachers faced various challenges as they tried to implement PBL, but the most common barrier discussed by interviewees was the lack of awareness of parents and principals towards PBL among others. Finally, the study concluded that the reason teachers lie at the two extremes of the Child Adults Involvement Continuum could be due to their views towards PBL, its benefits, and the challenges they face in implementing it. The study contributes to the ongoing research on how PBL is conceived and integrated into the pre-primary school context through the Eritrean perspective. The findings can inform future professional development for practitioners.